1991
DOI: 10.1192/bjp.158.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Pharmacodynamics of Physostigmine in Alzheimer's Disease Investigated Using Single-Photon Computerised Tomography

Abstract: The effects of physostigmine on patterns of rCBF in patients with pre-senile Alzheimer's disease were studied using 99mTc-labelled HMPAO SPECT. Regional CBF increased in the left cortex relative to right, with the most significant effect in left frontal and higher frontal regions. Measures of regional brain function, such as SPECT, are an important complement to psychological test batteries in understanding the effects in brain of putative antidementia drugs. SPECT brain imaging could extend our understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…Although attentional performance was not measured in our patients, treatment with donepezil may have a similar effect in responders without relative frontal hypoperfusion. Some studies have shown that cholinesterase inhibitors improve rCBF in patients with AD, with the most significant effect in the frontal region [26,27]. Cholinesterase inhibitors have previously been shown to generally improve rCBF in ischemic rat brains, but no improvements in rCBF at the ischemic core have been reported [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although attentional performance was not measured in our patients, treatment with donepezil may have a similar effect in responders without relative frontal hypoperfusion. Some studies have shown that cholinesterase inhibitors improve rCBF in patients with AD, with the most significant effect in the frontal region [26,27]. Cholinesterase inhibitors have previously been shown to generally improve rCBF in ischemic rat brains, but no improvements in rCBF at the ischemic core have been reported [28].…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil also improved psychomotor speed and attention as well as memory in patients with Parkinson's disease [41]. Furthermore, AD patients with lower perfusion in the orbitofrontal cortex may respond behaviorally to ChEI [8], and a short-acting ChEI, physostigmine, may in turn increase frontal perfusion [42]. Taken together, executive dysfunction caused by HBP, PVH, AD per se or even Parkinson's disease may be likely to respond to donepezil through improvement of the frontal-subcortical cholinergic interaction [7].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now only few activation studies have been per formed in (S)DAT [36][37][38][39][40][41][42][43][44][45]. Those using physostigmine infusion as stimulus [36][37][38][39][40] described an increased CBF following drug administration in patients.…”
mentioning
confidence: 99%
“…Those using physostigmine infusion as stimulus [36][37][38][39][40] described an increased CBF following drug administration in patients. However, only one of these studies had a control group and revealed an increase of CBF only in the patient group [39], but there was a 1-week time interval between the investigations.…”
mentioning
confidence: 99%